Tes Toleransi Glukosa Oral Ibu Hamil Trimester II dan III Di Puskesmas Way Halim Bandar Lampung - Nabella Putri Munggaran; Fonda Octarianingsih; Festy Ladyani; Bambang Kurniawan (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Oral Glucose Tolerance Test is a method used to help diagnose Diabetes Mellitus. Purpose: knowing the picture of blood glucose in trimester II and III pregnant women at Way Halim Puskesmas Bandar Lampung in 2019-2020. Method: using descriptive-analytic research using a descriptive approach to determine the description of blood glucose in pregnant women trimester II and III. The sampling technique uses a total sampling method, with a minimum sample size of 30 samples. Results: Oral Glucose Tolerance Tests for second and third trimester pregnant women obtained fasting blood glucose mg/dl and after oral Glucose Tolerance Test obtained 26.67% (4 people) which <90 mg/dl. The average age of pregnant women <35 years, BMI in second-trimester pregnant women has a normal body mass index. The parity picture of trimester II and III pregnant women is nulliparous (<1 child) in trimester II pregnant women as many as 10 people (66.67%) and trimester III pregnant women as many as 9 people (60%). History of abortion, pregnant women trimester II and trimester III have no history of abortion (100%), pregnant women trimester II and trimester III have no history of Gestational Diabetes Mellitus (100%). Family history of diabetes mellitus, trimester II and III pregnant women have a family history of diabetes, 7 people (46.67%) in trimester II pregnant women and 6 people (40%) in trimester III pregnant women. History of child macrosomia, trimester II and III pregnant women have a history of macrosomia, but only 1 person from the total sample is minimal. Each trimester II pregnant women as many as 14 people (93.3%), 15 people (100%) and third trimester as many as 15 people (100%)